Competitive Illusion as a Cause of Business Cycles - Mitchell, Thomas Warner (Quarterly Journal of Economics, 1924)
Supplies come on the market, not as quantities available for sale, but as flow responding to demand, 632. — Manufacturers' usual practice is to "sell then make, " not "make for stock, " 634. — Details of the "sell-then-make" policy, 635. — The "make-for-stock" policy sometimes followed in part; its virtues, 636. — Connection of the sell-then-make policy with business cycles, 642. — Demands from distributers bring response in production, 642. — If products are not forthcoming, orders are exaggerated or duplicated, 645. — False demands lead to over-enlargement of supplies, 647. — Reaction. Alternate exaggeration and understatement of consumers' demands, 648.